Long-Term Outcomes for Patients with Prostate Cancer Having Intermediate and High-Risk Disease, Treated with Combination External Beam Irradiation and Brachytherapy. (28th July 2010) - Dattoli, Michael; Wallner, Kent; True, Lawrence; Bostwick, David; Cash, Jennifer; Sorace, Richard
Abstract : Background . Perception remains that brachytherapy-based regimens are inappropriate for patients having increased risk of extracapsular extension (ECE). Methods . 321 consecutive intermediate and high-risk disease patients were treated between 1/92 and 2/97 by one author (M. Dattoli) and stratified by NCCN guidelines. 157 had intermediate-risk; 164 had high-risk disease. All were treated using the combination EBRT/brachytherapy± hormones. Biochemical failure was defined using PSA> 0.2 and nadir +2 at last followup. Nonfailing patients followup was median 10.5 years. Both biochemical data and original biopsy slides were independently rereviewed at an outside institution. Results . Overall actuarial freedom from biochemical progression at 16 years was 82% (89% intermediate, 74% high-risk) with failure predictors: Gleason score( P = .01 ) and PSA( P = .03 ) . Hormonal therapy did not affect failure rates( P = .14 ) . Conclusion . This study helps to strengthen the rationale for brachytherapy-based regimens as being both durable and desirable treatment options for such patients. Prospective studies are justified to confirm these positive results.